Visual Search in Chinese Children With Attention Deficit/Hyperactivity Disorder and Comorbid Developmental Dyslexia: Evidence for Pathogenesis From Eye Movements - Cui, Xiaohui; Wang, Jiuju; Chang, Yulin; Su, Mengmeng; Sherman, Hannah T.; Wu, Zhaomin; Wang, Yufeng; Zhou, Wei (Frontiers in Psychology, 2020)
In this study, a visual search task was conducted on children with comorbid attention deficit/hyperactivity disorder (ADHD) and development dyslexia (DD), pure ADHD, and typically developing children to explore the pathogenesis of comorbidity be-tween ADHD and DD. Participants searched for the target character from five char-acters in each trial during the task. The distractors included orthographically similar characters, homophones, unrelated characters and characters of a different color (i.e., red). Results showed that the clinical groups produced longer first fixation duration than the control group in all types of distractors. Children with ADHD comorbid DD were also more susceptible to characters with the distracting red color in gaze dura-tion and total viewing time than children with pure ADHD and healthy controls. The implication of comorbidity (ADHD + DD) on the pathogenesis was discussed. These results may be helpful for the diagnosis and treatment of ADHD with comorbid DD.